The Potential of CRISPR/Cas9 Gene Editing as a Treatment Strategy for Inherited Diseases - Abdelnour, Sameh A.; Xie, Long; Hassanin, Abdallah A.; Zuo, Erwei; Lu, Yangqing (Frontiers in Cell and Developmental Biology, 2021)
Clustered regularly interspaced short palindromic repeats (CRISPR) is a promising innovative technology for genomic editing that offers scientists the chance to edit DNA structures and change gene function. It has several possible uses consisting of editing inherited deficiencies, treating, and reducing the spread of disorders. Recently, reports have demonstrated the creation of synthetic RNA molecules and supplying them alongside Cas9 into genome of eukaryotes, since distinct specific regions of the genome can be manipulated and targeted. The therapeutic potential of CRISPR/Cas9 technology is great, especially in gene therapy, in which a patient-specific mutation is genetically edited, or in the treating of human disorders that are untreatable with traditional treatments. This review focused on numerous, in vivo, in vitro, and ex vivo uses of the CRISPR/Cas9 technology in human inherited diseases, discovering the capability of this versatile in medicine and examining some of the main limitations for its upcoming use in patients. In addition to introducing a brief impression of the biology of the CRISPR/Cas9 scheme and its mechanisms, we presented the utmost recent progress in the uses of CRISPR/Cas9 technology in editing and treating of human genetic diseases.